2022
DOI: 10.1093/mnras/stac3081
|View full text |Cite
|
Sign up to set email alerts
|

A multiwavelength study of multiple spectral component jets in AGN: testing the IC/CMB model for the large-scale-jet X-ray emission

Abstract: Over ∼150 resolved, kpc-scale X-ray jets hosted by active galactic nuclei have been discovered with the Chandra X-ray Observatory. A significant fraction of these jets have an X-ray spectrum either too high in flux or too hard to be consistent with the high-energy extension of the radio-to-optical synchrotron spectrum, a subtype we identify as Multiple Spectral Component (MSC) X-ray jets. A leading hypothesis for the origin of the X-rays is the inverse-Compton scattering of the cosmic microwave background by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 144 publications
(198 reference statements)
0
6
0
Order By: Relevance
“…The X-ray emission feature, located a few arcsecs away from the quasar core, was previously interpreted as IC/CMB radiation. This source appeared in the Fermi/LAT 4FGL 8-year point source catalog and this data was used to estimate the flux upper limits in gamma rays [19]. The study finds that IC/CMB model is ruled out for interpreting the X-ray emission considering the gamma-ray flux upper limit estimates.…”
Section: J1510+5702mentioning
confidence: 99%
See 1 more Smart Citation
“…The X-ray emission feature, located a few arcsecs away from the quasar core, was previously interpreted as IC/CMB radiation. This source appeared in the Fermi/LAT 4FGL 8-year point source catalog and this data was used to estimate the flux upper limits in gamma rays [19]. The study finds that IC/CMB model is ruled out for interpreting the X-ray emission considering the gamma-ray flux upper limit estimates.…”
Section: J1510+5702mentioning
confidence: 99%
“…The resolved X-ray jet of PKS J1421-0643 (at 𝑧 = 3.69) and PSO J030947.49+271757.31 (𝑧 = 6.1) were modelled with the IC/CMB interpretation [17,18]. Recently, Breiding et al [19] examined the IC/CMB interpretation for 45 extra-galactic X-ray jets. They found that the IC/CMB model is questioned in 27 Multi-Spectral Component (MSC) X-ray jets due to over-prediction for the observed MeV-to-GeV 𝛾-ray flux.…”
Section: Introductionmentioning
confidence: 99%
“…[75,76] for review. Within more recent years, however, IC-CMB models have been disfavoured in an increasing number of sources as they tend to, e.g., over-predict Fermi-LAT gamma-ray flux limits [77,78] or are not supported by detailed X-ray spectral information [79]. An electron synchrotron origin, however, requires to maintain electrons with Lorentz factors γ e ∼ 10 8 all along the jet.…”
Section: Understanding the Large-scale Jet Emission Of Agnsmentioning
confidence: 99%
“…However, through the use of a recombined light-curve analysis, Meyer and Georganopoulos (2014) first showed that the IC/CMB model could be strongly ruled out through gamma-ray upper limits for the X-ray jet of 3C 273, before doing the same in PKS 0637-752 (Meyer et al 2015(Meyer et al , 2017. Peter Breiding then widely applied this test to essentially all the 'multiple spectral component' or MSC jets for his PhD thesis work (Breiding et al 2017(Breiding et al , 2023, finding that 24/45 sources tested would require IC/CMB-predicted GeV emission significantly in violation of the gamma-ray limits (see example SEDs for two of the sources from Breiding et al (2023) in Figure 2).…”
Section: The Rise and Fall Of The Ic/cmb Modelmentioning
confidence: 99%